2017
DOI: 10.1155/2017/6312514
|View full text |Cite
|
Sign up to set email alerts
|

Immune Responses to Tissue-Restricted Nonmajor Histocompatibility Complex Antigens in Allograft Rejection

Abstract: Chronic diseases that result in end-stage organ damage cause inflammation, which can reveal sequestered self-antigens (SAgs) in that organ and trigger autoimmunity. The thymus gland deletes self-reactive T-cells against ubiquitously expressed SAgs, while regulatory mechanisms in the periphery control immune responses to tissue-restricted SAgs. It is now established that T-cells reactive to SAgs present in certain organs (e.g., lungs, pancreas, and intestine) are incompletely eliminated, and the dysregulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 101 publications
0
23
0
Order By: Relevance
“…Moreover, the ECM functions as reservoir of proteins (cytokines and analogues) critical for the tissue's welfare that are released or stored depending on the tissue's metabolic needs. Interestingly, the ECM retains most of these factors throughout decellularization, a process by which ECM scaffolds are generated. This process, first described in the 1960s , aims to completely eliminate the cellular compartment of tissues and organs, including its DNA and RNA content, and can nowadays be successfully and consistently applied to virtually all mammal tissues and organs of clinical interest .…”
Section: Utility Of Scaffolding Materialsmentioning
confidence: 99%
“…Moreover, the ECM functions as reservoir of proteins (cytokines and analogues) critical for the tissue's welfare that are released or stored depending on the tissue's metabolic needs. Interestingly, the ECM retains most of these factors throughout decellularization, a process by which ECM scaffolds are generated. This process, first described in the 1960s , aims to completely eliminate the cellular compartment of tissues and organs, including its DNA and RNA content, and can nowadays be successfully and consistently applied to virtually all mammal tissues and organs of clinical interest .…”
Section: Utility Of Scaffolding Materialsmentioning
confidence: 99%
“…Their group have introduced the concept of the 'two hit' hypothesis for the development SAGs. The initial 'hit' involves an initial lung injury as a result of triggers such as infections with community acquired respiratory viruses (CARV), gastro-oesophageal reflux disease (GORD), ischaemia-reperfusion injury, or even the presence of HLA-DSA (91,92). The resulting local inflammatory response exposes SAGs such as Col-V and Kα1T which stimulate up-regulation of self-reactive lymphocytes and non-HLA antibody production.…”
Section: Pathophysiology Of Amrmentioning
confidence: 99%
“…The second 'hit' is a result of down-regulation of regulatory T cells (TREGS) with loss of inhibition of self-reactive lymphocytes against SAGs which would usually induce T cell tolerance to SAGs. This ultimately leads to SAG autoimmunity Bharat (91,93). These SAGs may be a significant contributing factor to ongoing CLAD in patients who clear DSA post AMR treatment using commercially available kits that do not measure SAGs.…”
Section: Pathophysiology Of Amrmentioning
confidence: 99%
“…69,72,73,171 Although dogma states that self-reactive lymphocytes are deleted in the thymus, recent research has suggested that tissuerestricted SAgs are not expressed on thymocytes. 194 Therefore, it is the responsibility of Tregs to suppress self-reactive lymphocytes against tissue-specific SAgs. 194 It stands to reason that lung allograft injury, when combined with a loss of Tregs, would lead to lung-restricted autoimmunity (LRA).…”
Section: Lung-restricted Autoimmunity and Cladmentioning
confidence: 99%
“…194 Therefore, it is the responsibility of Tregs to suppress self-reactive lymphocytes against tissue-specific SAgs. 194 It stands to reason that lung allograft injury, when combined with a loss of Tregs, would lead to lung-restricted autoimmunity (LRA). Respiratory viral infections can injure pulmonary epithelium, downregulate Tregs, and result in de novo LRA.…”
Section: Lung-restricted Autoimmunity and Cladmentioning
confidence: 99%